Genotypic characterization of β-lactamase resistant Salmonella species isolated from different quail houses and their susceptibility to extracts of thyme and chitosan, and Saccharomyces Cerevisiae - Halla E.K. El Bahgy; Mohamed Mohamed Soliman; Helal F. Al-Harthi; Enas A. Soliman (Journal of Applied Animal Research)
This study aimed to identify Salmonella species in two systems for quail raising (deep litter system and cages system). Determination of antibiotic susceptibility, β-lactamase resistance genes profile and susceptibility to chitosan, thyme extract and S. cerevisiae was examined. Fifteen Salmonella isolates were isolated from eighty cloacal swabs examined, with a higher incidence from those of deep litter systems than cage housing systems. Regarding the environmental samples, Salmonella was higher in the deep litter system than in cage housing. Serological identification of 27 salmonella isolates typed them into 8 Salmonella spp. including S. Tsevie, S. Infantis, S. Kentucky, S. Typhimurium, S. Larochelle, S. Molade, S. Enteritidis and S. Labadi. The profile of β-lactamase-resistance genes revealed the presence of blaTEM and blaSHV genes in S. Typhimurium and S. Infantis; blaTEM and blaCTX-M1 genes in S. Enteritidis and S. Molade, while S. Kentucky and S. Tsevie were positive for the blaCTX-M1 gene only. S. Larochelle was negative for all of them. Thyme and chitosan extract showed that S. cerevisiae had the highest inhibitory activity against the tested strains. In conclusion, farms with superior biosecurity and hygiene practices will reduce the risk of pathogens and eliminate the need for prophylactic antibiotics, thereby preventing antibiotic resistance.